Improved therapeutic antibody delivery to xenograft tumors using cavitation nucleated by gas-entrapping nanoparticles - Grundy, M; Bau, L; Hill, C; Paverd, C; Mannaris, C; Kwan, J; Crake, C; Coviello, C; Coussios, C; Carlisle, R (Future Medicine, 2021)
Aims: Testing ultrasound-mediated cavitation for enhanced delivery of the therapeutic antibody cetuximab to tumors in a mouse model. Methods: Tumors with strong EGF receptor expression were grown bilaterally. Cetuximab was coadministered intravenously with cavitation nuclei, consisting of either the ultrasound contrast agent Sonovue or gas-stabilizing nanoscale SonoTran Particles. One of the two tumors was exposed to focused ultrasound. Passive acoustic mapping localized and monitored cavitation activity. Both tumors were then excised and cetuximab concentration was quantified. Results: Cavitation increased tumoral cetuximab concentration. When nucleated by Sonovue, a 2.1-fold increase (95% CI 1.3- to 3.4-fold) was measured, whereas SonoTran Particles gave a 3.6-fold increase (95% CI 2.3- to 5.8-fold). Conclusions: Ultrasound-mediated cavitation, especially when nucleated by nanoscale gas-entrapping particles, can noninvasively increase site-specific delivery of therapeutic antibodies to solid tumors.